EVPN in the data center - Dutt, Dinesh G. (O'Reilly Media, 2018)
Ethernet VPN (EVPN) has recently been gaining support among companies looking to solve problems in the design of data center networks. This mature technology has been a part of service provider networks for years, but data center network architects and operators have to contend with complex concepts and terminology spread across multiple standards documents to piece together the relevant model for their data center. This practical ebook cuts through the fog to explain how you can deploy this technology in the core of your data center. By guiding you through EVPN concepts and practicalities, author Dinesh Dutt (BGP in the Data Center) illustrates why this technology is the piece you need to successfully adopt VXLAN in your Clos-based network. You'll also discover why EVPN can be simpler to use in data centers than in service provider networks. Understand network virtualization overlays (NVO) and network tunneling Learn the constructs that Border Gateway Protocol (BGP) provides to support NVOs Understand how bridging works in EVPN networks, including the behavior with dual-attached hosts Examine different routing models with EVPN Inspect the most common deployment scenarios in EVPN configuration and put them to use in other situations.